2017
DOI: 10.1039/c7ra06824g
|View full text |Cite
|
Sign up to set email alerts
|

N,N-Dimethylpyridin-4-amine (DMAP) based ionic liquids: evaluation of physical properties via molecular dynamics simulations and application as a catalyst for Fisher indole and 1H-tetrazole synthesis

Abstract: The last few decades have seen a rapid increase in the use of ionic liquids (ILs) as a green alternative to traditional solvents in organic synthesis. The use of ILs as catalysts has also increased in recent years.Herein we the report synthesis of new N,N-dimethylpyridin-4-amine (DMAP) based ionic liquids (ILs) as new and efficient catalysts for the facile synthesis of indoles (via Fischer indole synthesis), and 1H-tetrazoles (via click chemistry). The method is environmentally friendly, requiring only minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The quinine ionic liquids produced higher yields than traditional bases (Table 3 entries 9, 10) and quinine itself (Table 3 entry 8). This suggests that the molecular functionality of the catalyst is important and it does not act solely as a base.…”
Section: Quinine Ionic Liquids As Basic Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quinine ionic liquids produced higher yields than traditional bases (Table 3 entries 9, 10) and quinine itself (Table 3 entry 8). This suggests that the molecular functionality of the catalyst is important and it does not act solely as a base.…”
Section: Quinine Ionic Liquids As Basic Catalystsmentioning
confidence: 99%
“…Basic ionic liquids of greater stability can be prepared by locating basicity on the cation [5], usually on free Lewis basic sites. Examples of this class includes ionic liquids synthesised from diaminoalkanes [6] and 4-dimethylaminopyridine (DMAP) [7,8]. Diaminoalkane ionic liquids suffer from a lack of selective alkylation which complicates their synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DES, the ionic liquids and HBDs are associated to each other via hydrogen bonded networks, molecular dynamics (MD) simulations were used to study these interactions. Moreover, macroscopic properties, like transport and thermodynamic behaviour, as well as microscopic properties such as density, viscosity and effect of non‐bonded interaction on structural framework of ILs were also extensively studied via molecular dynamics simulations ,. In literature, only a limited number of simulation studies on DES were reported, that mainly focus on the understanding of interactions, such as electrostatic and hydrogen bonding, that confer unique characteristics to DES .…”
Section: Introductionmentioning
confidence: 99%
“…Transport properties of DES mixtures are of great importance due to their diverse applications which are based on these properties. In our previous studies, on ionic liquids, transport properties were determined by calculating mean square displacement (MSD), which was then used to compute diffusion coefficients for cations and anions. A similar method was adopted herein to calculate MSD for morpholinium based cation MoBr (C 7 ), bromide ion and HBDs in different DES mixtures.…”
Section: Introductionmentioning
confidence: 99%